Reactive Power Compensation Techniques and Reporting in Electrical Networks - Alakbarov, Mukhtar (ADA University, 2024)
Integrating renewable energy sources into the modern grid has been challenging in terms of maintaining grid stability and quality. Changes in renewable energy production and fluctuating load demands have brought innovative methods for reactive power compensation. This thesis discusses some adaptive reactive power compensation algorithms for renewable energy integration and evaluates their effects on grid stability and efficiency. The main purpose of this thesis is to present an adaptive reactive power compensation model that can dynamically adapt to changes in the grid. Advanced control algorithms that can provide maximum power quality are targeted with STATCOM, which is selected as the main compensation device. Within the scope of the research, the responses of STATCOM under active grid conditions and the innovations in the grid to which it is added at certain periods are investigated through simulation and calculation. Adaptive control philosophy will be simulated using DIgSILENT to evaluate its performance by looking at basic values such as voltage sharpness, power factor optimization and energy efficiency, and necessary comparisons will be made and visuals will be provided with graphics. In addition, within the scope of this thesis, it will be investigated how a STATCOM can make a difference in performance compared to classical compensation devices in terms of its advantages in cases where renewable energy is of high importance. The results obtained in all these stages show that the proposed adaptive control strategies significantly increase the stability of the grid, especially under sudden changes in renewable energy output. The important results obtained as a result of the thesis studies emphasize the importance of adding intelligent control systems to reactive power management for future electrical grids. The innovative contributions in this thesis are threefold: comprehensive analysis of the limitations of conventional techniques, formulation of an adaptive algorithm specifically for renewable energy grids, and performance evaluation by proposing a framework for multiple scenarios. Furthermore, by investigating the possibility of reduced losses with a STATCOM-based system compared to conventional methods, this thesis further emphasizes energy efficiency. The research conducted in this study provides valuable insights into adaptive reactive power compensation and its vital role in supporting the transition to sustainable energy systems. The proposed framework not only addresses the urgent challenges of renewable energy integration, but also lays a foundation for future work in the field of smart grid technologies and smart energy management systems. The current work bridges the gap between theoretical development and practical application by proposing a robust solution to improve grid stability in the renewable era.
Keywords: Grid stability; Renewable energy integration; Smart grid technologies; IT and Engineering